The implementation of artificial intelligence (A.I.) in the hospital pharmacy: The application of quality assurance/quality initiatives (QA/QI) cycle (the problem-solving approach) / Dr Nur Wahida Zulkifli - Zulkifli, Nur Wahida (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
In recent years, there has been a noticeable surge in interest in the applications of A.I. technology for understanding and analysing several significant areas of pharmacy, including drug development, dosage form design, polypharmacology, and hospital pharmacy. Several countries are currently embracing the regular deployment of A.I. in their hospital pharmacies. This is because there are four key functional segments that constitute the foundation of A.I.-based online hospital pharmacy services: online drug list retrieval, prescription preview, drug dispensing and distribution, and online medication consultation. These segments play a crucial role in ensuring the safe and rational use of medications while also saving patients' time and money. Furthermore, applying the QA/QI cycle is crucial to better understand the issues that A.I. is intended to tackle, thereby improving its utilization in hospital pharmacy systems. It is essential to recognize that different hospitals may face different problems and require tailored solutions. The QA/QI cycle involves identifying issues with the way care is delivered and implementing corrective measures to address them. The majority of QA/QI efforts are reactive and retrospective, with improvement efforts focused on raising the level of quality to meet predefined standards.